Análise paisagística dos parques de bairro de Santa Maria - Lautert, Alice Rodrigues (2020)
Urban parks are free spaces for leisure, recreation and circulation that contribute to the quality of urban life. This research sought to analyze, through landscaping, the neighborhood parks in the middle city of Santa Maria, RS. The parks selected for this study were the existing and active parks of this category in the city: Itaimbé Park, Medianeira Park, CACISM Park and Jockey Club Park. The role of these parks within the Santa Maria Free Spaces System was investigated and quantitative and qualitative analysis methodologies were applied: landscape characterization, identification of Landscape Units and Subunits, Behavioral Map and application of questionnaires. So, it was possible to characterize its social, natural and constructed elements, as well as observe the different types of users, usage patterns, activities performed, levels of physical activities and social interactions in each park and understand the users' perception of these spaces. After conducting the internal diagnosis of the parks, a comparative assessment was made in which their similarities and divergences, deficiencies and potentialities were identified and, subsequently, proposals for planning and project requalification of the parks were identified. It was found that neighborhood parks suffer from neglect, lack of maintenance and planning. However, they have a relevant role within the Santa Maria Free Spaces System, promoting public life, social interactions and leisure and recreation activities for the population